PARTISIPASI GURU SEKOLAH DASAR DALAM PENERAPAN KAWASAN TANPA ROKOK DI SEKOLAH - , Halyani, Dra. Yayi Suryo Prabandari, M.Si, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The teacher as a person who is considered important in many school environments influence the formation of attitudes and behavior of students towards something. The desire to smoke on the students because by inspired of behavior parent and teacher who smoke. The successful implementation of the program and development of smoke free area in comprehensive schools is inseparable from the attitude of teachers to support and active participation of teachers in the program. In Ternate, almost all primary schools are teachers who smoke at school. Objective: To determine the participation of primary school teachers in the introduction of priority issues or problems, teacher participation in the determination of problem solving or planning on applying smoke free area in school. In addition, to determine perceptions of elementary school teachers in the expected results in the application of smoke free area in school. Method: This study was a qualitative research using the case study method of respondent selection strategy was sampling with maximum variation. The number of respondents in focus group discussions as many as 44 people, divided into 7 groups. Respondents in-depth interviews as many as 11 people. Data were collected by observation, focus group discussions and in-depth interviews. Data analysis is data collection, data reduction, data presentation and data verification or drawing conclusions. Results: The implementation of smoke free area is still limited to introduction and problem solving. All participated in the implementation of smoke free area, including teacher smoking status. Teacher's perception that cigarettes have negative effects on health and the need for the application of smoke free area in school. Regulation of smoke free area there is no at school. Therefore, the cooperation required by the government to issue a regulation on the smoke free area in school. Conclusion: Smoke free area application can be implemented in schools, if there is cooperation of various parties and the regulation of moke free area at school.